How Gender Integration Can Reduce the Income-Inequality Gap - Ritu Srivastava; Surbhi Cheema (Australasian Accounting, Business and Finance Journal, 2019)
The labour force participation rates in India stands at 27.2 % for women in comparison to 78.8% for men whereas globally, the gender gap in the labour force participation rate is 26.5% as per the report published by ILO (2017). The employment conditions are also reported to be vulnerable for the women in terms of fewer working hours; usually not by choice, access to social protection and ambiguous employment contract. Gender integration in the workforce is facilitated through developmental policies of the government such as cluster development and associated “rurbanisation” i.e. transformation of rural to urban areas. Sustainable economic growth requires greater women participation for the enhanced income of these “rurban” areas. Even though the economic necessity may lead to no choice but to work; for women, the gains from income may not lead to her overall well-being. To optimize these results of socio-economic policies, the policy-makers should be able to gauge the benefits as well as the loop-holes of investment and its impact on human development. This study assesses whether the stimulation to local economic development through income generation leads to narrowing gaps in areas of income, literacy and gender gap in the workforce. The paper also uses textual analysis to explore the idea and perception of gender integration at the workplace of the women natives of the rurban clusters of Greater Noida which has undergone a shift in the structure of its major economic activities. The study presents the perceptual findings of women and their preference towards work the balance between work and family, similar opportunities as men and obstacles at work. The socio-economic development of women is assessed to examine the role of rurbanisation in reducing the income-inequality gap.
Keywords: India; gender integration; rururbanisation; workforce participation; income inequality gap.